Structural and functional characteristics of selected soft wheat starches - Franco, CML; Wong, K. S.; Yoo, S. H.; Jane, J. L. (Amer Assoc Cereal Chemists, 2002)
Starches from eight soft wheat samples (two parent lines and six offspring) were isolated; relationships between their structures and properties were examined. Branch chain-length distributions of amylopectins were determined by using high-performance anion exchange chromatography equipped with an amyloglucosidase reactor and a pulsed amperometric detector (HPAEC-ENZ-PAD). Results showed that the average chain length of the eight samples varied at DP 25.6-26.9. Starch samples of lines 02, 60, 63, 95, and 114 consisted of amylopectins with more long chains (DP greater than or equal to 37) and longer average chain length (DP 26.2-26.9) than that of other samples. These starch samples of longer branch chain length displayed higher gelatinization temperatures (55.3-56.5degreesC) than that of other samples (54.4-54.9degreesC) and higher peak viscosity (110-131 RVU) and lower pasting temperature (86.3-87.6degreesC) than others (83-100 RVU and 88.2-88.9degreesC, respectively). The M-w of amylopectins, determined by using high-performance size exclusion chromatography equipped with multiangle laser-light scattering and refractive index detectors (HPSEC-MALLS-RI), were similar for all samples (6.17 x 10(8) to 6.97 x 10(8)). There were no significant differences in amylose and phosphorus contents between samples. These results indicated that physical properties of wheat starch were affected by the branch-chain length of amylopectin.